2010
DOI: 10.1002/jbmr.93
|View full text |Cite
|
Sign up to set email alerts
|

High-phosphate-induced calcification is related to SM22α promoter methylation in vascular smooth muscle cells

Abstract: Hyperphosphatemia is closely related to vascular calcification in patients with chronic kidney disease. Vascular smooth muscle cells (VSMCs) exposed to high phosphate concentrations in vitro undergo phenotypic transition to osteoblast-like cells. Mechanisms underlying this transdifferentiation are not clear. In this study we used two in vitro models, human aortic smooth muscle cells and rat aortic rings, to investigate the phenotypic transition of VSMCs induced by high phosphate. We found that high phosphate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Several studies provide support for the idea that SMC differentiation marker gene expression is regulated by DNA methylation. For example, the decrease in SM22 expression observed in human SMCs treated with high phosphate was associated with increased SM22 promoter methylation 44 while SM22 methylation was decreased in multipotential adventitial cells that were induced to differentiate into SMC 45 . Hu et al has also shown that SM α-actin expression in fibroblasts inversely correlated with DNA methylation near the SM α-actin transcription start site 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provide support for the idea that SMC differentiation marker gene expression is regulated by DNA methylation. For example, the decrease in SM22 expression observed in human SMCs treated with high phosphate was associated with increased SM22 promoter methylation 44 while SM22 methylation was decreased in multipotential adventitial cells that were induced to differentiate into SMC 45 . Hu et al has also shown that SM α-actin expression in fibroblasts inversely correlated with DNA methylation near the SM α-actin transcription start site 46 .…”
Section: Discussionmentioning
confidence: 99%
“…β-Glycerophosphate seems to induce ALP consistently when used as a component of calcification medium for VSMCs, and this induction is potentiated by the addition of other procalcific agents [6,8,30,31,41,42]. Experimental setups with other phosphate donors have demonstrated both stimulatory, [43,44] absent [45] or even inhibitory [46] effects on ALP activity in calcifying VSMCs. Prosdocimo et al [45] found a rapid, ALP-independent reduction of extracellular pyrophosphate in calcifying rat VSMCs stimulated with cAMP and phosphate salts, which was associated with the downregulation of the pyrophosphate membrane transporter ANK.…”
Section: Discussionmentioning
confidence: 99%
“…The increased methylation resulted in reduced expression of SM22α, increased Runx2 expression, and increased ALP activity, which together resulted in an increased level of calcification. 67 Inhibition of DNA methylation by procaine was able to prevent these transcriptional changes when VSMCs were grown in high P media, and this resulted in reduced calcification.…”
Section: Direct Effects Of High P On Pathways Mediating Vsmc Calcificmentioning
confidence: 99%